2021
DOI: 10.1021/jacs.1c07795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Molybdenum Disulfide Defect Photoluminescence Quenching by Adsorbed Metallophthalocyanines

Abstract: Lattice defects play an important role in determining the optical and electrical properties of monolayer semiconductors such as MoS 2 . Although the structures of various defects in monolayer MoS 2 are well studied, little is known about the nature of the fluorescent defect species and their interaction with molecular adsorbates. In this study, the quenching of the low-temperature defect photoluminescence (PL) in MoS 2 is investigated following the deposition of metallophthalocyanines (MPcs). The quenching is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Amsterdam et al recently demonstrated by gate voltage-dependent measurements and DFT calculations that organic macromolecules, as MPcs can stabilize the negatively charged defects in the MoS 2 lattice. 55 Indeed, they found that the positive electrostatic potential of the outer carbon ring of the MPc sitting above the MoS 2 defects stabilizes its negative charge. CoPc (7.46 eV) having higher E I compared to H 2 Pc (7.36 eV) 67 was found as the best stabilizer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amsterdam et al recently demonstrated by gate voltage-dependent measurements and DFT calculations that organic macromolecules, as MPcs can stabilize the negatively charged defects in the MoS 2 lattice. 55 Indeed, they found that the positive electrostatic potential of the outer carbon ring of the MPc sitting above the MoS 2 defects stabilizes its negative charge. CoPc (7.46 eV) having higher E I compared to H 2 Pc (7.36 eV) 67 was found as the best stabilizer.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the adsorption of PAHs induces a significant defect healing, as evidenced by the reduction of the peak contributions of the S 2p defect component and the Mo 4+ 3d 5/2 d and Mo 4+ 3d 3/2 d. The healing appeared to be more effective in the order pyrene < phenanthrene < naphthalene, as shown in Table S1. The functionalization of 2D TMDCs with different molecules has been extensively studied. For example, metallophthalocyanines (MPcs) are planar aromatic molecules coordinating a central atom in the inner ring, which are able to reduce the structural defects in TMDCs. In a similar fashion, in this work, the used planar PAHs appeared to be able to induce defect healing in the MoS 2 lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 180 ] Copyright 2021, American Chemical Society. E) Schematic illustration of the temperature‐dependent optical properties of BCPMoS 2 in hydrogel, as well as near‐infrared PT (photothermal) heating curves and IR thermal photographs of different nanocomposites.…”
Section: Electronic and Chemical Property Design Via Functionalizationmentioning
confidence: 99%
“…Low-temperature photoluminescence spectra of MoS 2 and MPcMoS 2 (right). Reproduced with permission [180]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%